IJCM_414A: Perception and pattern of usage of M- learning among medical students studying in Mangalore - Rekha T; Singh Chandini; Jain Abhishek; Salim Shahin; Parashar Rishi (Wolters Kluwer Medknow Publications, 2024)
Background: Mobile learning (M- learning) is the process of using a mobile device to access and study learning materials and to communicate with fellow students, instructors, or institutions. It can be utilized by both medical students as well as doctors to enhance educational and workplace activities, with the potential to enhance overall patient care and knowledge. This study aims to find out the perception of medical students towards the usage of M- learning in medical education and to determine the patterns of usage of M-learning among medical students. Methodology: This cross-sectional study was conducted among 469 students of Kasturba Medical College, Mangalore. The data was collected using a self- administered questionnaire- consisting of 2 sections: 1) General information of study participants 2) Perception of the mobile learning applications and its advantages and disadvantages. Data was analyzed using SPSS version 25. Descriptive statistics were expressed in mean (±SD), medians and percentages. Appropriate statistical tests were applied, and results were interpreted. P value > 0.05 was considered statistically significant. Results: The survey reveals a significant level of awareness and utilization of medical apps among medical students of the study settings, with 97.9% aware of their existence and 69.9% using them for educational purposes. More than half (55%) prefer smartphones for M-learning, primarily for reference (47.8%) and handy features (49.0%). The majority (76.0%) believe these apps save time and enhance knowledge (73.2%), express interest in college- specific apps (75.1%) and promote M-learning within the curriculum (60.8%). However, about 57.0% of students disagree with the usage of these app by non-medical personnel. Conclusions: This study demonstrates that M-learning is common among medical students and that it is utilized to supplement and expand the substantial amount of medical information that students must learn and comprehend.